Study On The Influence Of Shaft Material On Vibration In Rotating Machinery. (2018) - Chandrashekar, Gerald; Raj, Winston; Godwin, Charles; Paul, P. Sam
Abstract: Vibrations are an inherent phenomenon in rotating machineries. They are present in all types of machines and mechanical components. They are unwanted because they affect the optimal performance of these components and hence, it needs to be eliminated. Amongst the different parameters that affect vibration, selection of appropriate material is the most critical parameter. In this research paper, the effect due to the use of different types of shaft materials on vibration in rotating machinery is studied and the magnitude of vibration produced due to the use of different type of shaft material under the same condition of loads and rotational speeds was investigated. Shaft materials considered in this paper were stainless steel and mild steel and these materials were tested for Ball Bearing, Thrust Bearing and Tapered Roller Bearing. From experimental result, it was observed that mild steel gives the high amplitude of vibration for all the three bearings. Hence, it is preferable to use Stainless Steel than Mild Steel in rotational machineries due to its physical properties and lower vibration amplitude in varied conditions.